DURABILITY OF THE STABILIZED CLAY WITH LIME AND RICE HUSK ASH FOR ROADWAY SUBGRADE - Agus Setyo Muntohar, Roslan Hashim (Universitas Atma Jaya, 2008)
A stabilized soil should be durable in which has ability to retain its integrity and strength under service environmental condition. The determination of the durability properties of the soils mixtures is a problem since it is difficult to simulate in laboratory the detrimental action that is produced by weathering in the field. In this study, the durability test was determined by resisntance to immersion test according to BS 1924 – 1990: Section: 4.3. Two stabilised soils, clay and clayey-sand soils, with lime and rice husk as mixtures were tested. The investigation results show, in general, the stabilised soil loses the unconfined compressive strength subjected to the immersion. Loss in soil strength was owing to water intrusion into the soil and the soil adsorbed the water. Adding of lime and rice husk ash mixture is able to increase the resistance to immersion. Based on this study, addition 6% lime and 12 % rice husk ash show a good performance in unconfined compressive strength and durability. The laboratory test showed that the effect of immersion is dependent on the level of strength of pozzolanic reaction achieved prior to beginning of the period of soaking.